Choice in HIV testing: the acceptability and anticipated use of a self-administered at-home oral HIV test among South Africans. Issue 2 (15th July 2016) - Kelvin, Elizabeth A; Cheruvillil, Sonia; Christian, Stephanie; Mantell, Joanne E; Milford, Cecilia; Rambally-Greener, Letitia; Mosery, Nzwakie; Greener, Ross; Smit, Jennifer A
Abstract : Combination HIV prevention is being widely promoted by funders. This strategy aims to offer HIV prevention choices that can be selected and combined to decrease HIV risk in ways that fit with each individual's situation. Treatment as prevention and pre-exposure prophylaxis are two new evidence-based strategies to decrease HIV incidence, both of which require high HIV testing rates to be effective, and the Joint United Nations Programme on HIV/AIDS (UNAIDS) has set a goal of 90% of HIV-positive individuals knowing their status by 2030. However, HIV testing rates in many countries remain suboptimal. Just as no single HIV prevention method is ideal for all people in all situations, no single HIV testing modality is likely to be acceptable to everyone. By offering HIV testing choices, we may be able to increase testing rates. However, many low-resourced countries have been slow to take up new HIV testing options such as the self-administered at-home oral HIV test that is currently available in the United States. In this paper, we present findings from 20 in-depth interviews, conducted in 2010, documenting opinions about self-administered at-home oral HIV testing, a testing modality still largely unavailable in Africa. Participants were clients of three primary healthcare clinics in South Africa. Self-testing was seen as enabling confidentiality/privacy, saving time, and facilitating testing together with partners. However, concerns were raised about psychological distress when testing at home without a counsellor. Some suggested this concern could be minimised by having experienced clinic-based HIV testing and counselling before getting self-testing kits for home use. Thus, self-administered HIV testing could be an option added to the current testing modalities to address some important barriers to testing.